ESTIMATED PERFORMANCE FOR AGE: A NOVEL CRITERION FOR RETURN TO SPORT AFTER ANTERIOR CRUCIATE RECONSTRUCTION AND ITS PERFORMANCE COMPARED TO LIMB SYMMETRY INDICES. Issue 7 (30th July 2021) - Magill, John; Vance, Danica; Risoli, Thomas; Green, Cynthia; Reinke, Emily; Reiman, Michael; Thorburg, Kristian; Riboh, Jonathan
INTRODUCTION: The use of physical performance tests (PPT) for assessing readiness for return to sport (RTS) after ACL reconstruction in children is typically assessed based on a limb symmetry index (LSI). However, recent data show that: 1) healthy pediatric athletes have significant limb asymmetries at baseline and 2) the non-operative limb deconditions after ACLR, so return of LSI is not synonymous with return to pre-injury performance. We previously established a cohort of 100 healthy pediatric athletes and created growth curves for performance on 7 common PPT, allowing for the calculation of a performance percentile (PP) for any given individual based on their age. The current study explores the use of PP in a cohort of pediatric patients 6 months out from ACLR. We hypothesized that return to expected performance for age (EPFA, defined as the 50 th percentile of performance among healthy volunteers of a given age) would be a more stringent criterion than 90% LSI. METHODS: We performed a retrospective analysis of a prospective cohort of consecutive patients (< 19 years) undergoing ACL reconstruction between 2016-2019. Patients were excluded if they did not have RTS testing 6 months after surgery (+/- 6 weeks). RTS testing consisted of 7 PPT (Figure 1). Patients were then categorized into passing and failing groups based on two cutoffs: 1) LSI > 90% and 2) PP > EPFA (50 th percentile). The prevalence of passing based on these two criteria were compared using contingency analysis. A multivariable linear regression was performed to assess the effects of demographic variables on PP. RESULTS: Sixty-three patients were included (57% male, mean age 14.2 ± 2.4 years). Mean time from surgery to RTS testing was 181.5 ± 15.1 days. More patients were able to achieve 90% LSI than EPFA for all PPT except the timed hop (Figure 1). On average, 58% met LSI > 90% compared to only 41% meeting EPFA. Reaching 90% LSI correlated weakly with reaching EPFA for 4 of the 7 PPTs. However, of patients that would have passed based LSI, only 36.2-63.2% would have passed based on meeting EPFA (Figure 2). There was no consistent effect of age, sex, or graft type on PP. CONCLUSION: Six months after ACL reconstruction, fewer pediatric athletes can meet EPFA than can meet 90% LSI. Additionally, PP does not clearly correlate with LSI, suggesting that these criteria provide complementary information. Future studies investigating the use of EPFA as a cutoff for RTS are warranted. : Figure 1:. Prevalence of 50 th Performance Percentile and 90% Limb Symmetry Index (LSI) for each PPT Figure 2:. Prevalence of Above or Below the 50 th Performance Percentile for Patient that reached a passing LSI (90%).